Humanism and Theology in Renaissance Florence: four examples (Caroli, Savonarola, Ficino, and Pico) - Edelheit, Amos (Verbum – Analecta Neolatina, 2006)
The argument in this article is that we should not make clear-cut distinctions between humanism and philosophy or theology, and between the humanists and their contemporary scholastic theologians and philosophers, in the Florentine context of the second half of the fifteenth century. The relations between these two groups were complicated and included, beyond obvious differences, also mutual influences, not always discussed in detail among modern scholars. Starting from the known controversy between Eugenio Garin and Paul Oskar Kristeller regarding the nature of the humanist movement and its relations with philosophy, I then move-on to present four examples: the first two deal with "scholastic" theologians and preachers, the Dominicans Giovanni Caroli and Girolamo Savonarola, in whom I emphasize the humanist bias; the last two deal with humanist philosophers, Marsilio Ficino and Giovanni Pico della Mirandola, in whom I emphasize the importance of religion and theology for the understanding of their philosophy.